Role of Toll-Like Receptor 4 in Gram-Positive and Gram-Negative Pneumonia in Mice - Branger, Judith (American Society for Microbiology, 2004)
To determine the role of Toll-like receptor 4 (TLR4) in the immune response to pneumonia, C3H/HeJ mice (which display a mutant nonfunctional TLR4) and C3H/HeN wild-type mice were intranasally infected with either Streptococcus pneumoniae (a common gram-positive respiratory pathogen) or Klebsiella pneumoniae (a common gram-negative respiratory pathogen). In cases of pneumococcal pneumonia, TLR4 mutant mice showed a reduced survival only after infection with low-level bacterial doses, which was associated with a higher bacterial burden in their lungs 48 h postinfection. In Klebsiella pneumonia, TLR4 mutant mice demonstrated a shortened survival after infection with either a low- or a high-level bacterial dose together with an enhanced bacterial outgrowth in their lungs. These data suggest that TLR4 contributes to a protective immune response in both pneumococcal and Klebsiella pneumonia and that its role is more important in respiratory tract infection caused by the latter (gram-negative) pathogen.